Barriers and need for dataset sharing in the publishing of research thesis - Kumar, Atul; Gawande, Amol; Paliwal, Jaiprakash; Pendse, Vishwas; Kale, Shailendrakumar; Agarwal, Akash; Brar, Vinaydeep; Palav, Manesh; Nimbalkar, Sagar; Saini, Amandeep; Rathi, Gauri; Raibagkar, Shirish (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. This study aimed to understand the reasons for the non-sharing of datasets by Indian social science doctoral researchers and to determine whether researchers fully understand the significance of dataset sharing. Design/Methodology/Approach. A quantitative methodology was employed, entailing the administration of a questionnaire to 361 recent Indian doctoral recipients in the social sciences. The questionnaire comprised two sections: one ascertaining barriers to non-sharing of datasets and the other concerning the need of dataset sharing. Each section contained 10 statements, and responses were collected using a five-point Likert scale. Finally, a t-test was employed to ascertain if the sample means differed significantly from the population mean. Results/Discussion. Several barriers were identified that hinder the sharing of research datasets. These included the absence of specific provisions in the regulations of the Indian apex body (University Grants Commission [UGC]) for PhD research, the lack of encouragement from research supervisors and centers to share data, the exclusion of datasets during the final defense viva-voce, challenges in sharing datasets for reasons such as their non-existence or ad-hoc compilation, and the limited peer practice of dataset sharing. The average agreement for these barriers was 82%, which was statistically significant. Concurrently, researchers concurred with the need of dataset sharing, including enhanced transparency in the research process, improved reliability of research findings, facilitation of peer researchers’ comprehension of its structure and other salient details, harmonization of Indian research with international practices of data sharing, adherence to COPE norms on research ethics, and enhancement of thesis presentation during various forums, including the final defense viva-voce. The average agreement among researchers for these needs was 87%, which was statistically significant. Conclusions. Despite the global endorsement of data sharing as a highly desirable research practice, Indian researchers from the social sciences domain often face various challenges that prevent them from sharing their datasets. The non-sharing of datasets could raise concerns about the authenticity and reliability of research. Concurrently, the study indicated that researchers were aware of the advantages associated with data sharing. Collective action from the apex regulatory authority (UGC), research centers, research supervisors, and research scholars could lead to a desired improvement, particularly in the sharing of underlying datasets, which would enhance the reliability and transparency of research. Originality/value. This study represented a novel effort to comprehend the significant barriers to data-sharing practices in research within the context of Indian doctoral education in the social sciences and demonstrated that researchers exhibit a favorable disposition toward data sharing. This study contributed to the advancement of policy and practice regarding data sharing, with the objective of enhancing transparency, openness, and accountability in scientific research.